Upaya Pemberdayaan Masyarakat Dalam Pencegahan Stunting di Desa Randupitu Kabupaten Probolinggo - Mastina Maksin; Husni Mubaroq; Andhi Nur Rahmadi; Ariiqa Galuh Syaputri Salim; Dzikroyatul Hilwa; Muhammad Lutfi Fadlullah; Muhammad Salim (CV. ITTC INDONESIA, 2024)
Stunting is a serious problem for the world of health, especially in Indonesia. Factors that cause stunting, apart from lack of nutrition in babies, can also be caused by low education or lack of parental knowledge about stunting. Another factor is environmental health in the community and low economic conditions in the family so that the nutritional needs for the health of pregnant women and babies are not met. In 2023, the stunting rate in Randupitu Village reached 7 children, but in 2024 it fell to 3 children with 1 child already in the process of being repaired. Randupitu Village aspires to end the stunting rate by 2025 or Zero Stunting by 2025. The aim of this research is to describe the knowledge of mothers of toddlers and the community about stunting and what sources of information support the knowledge of mothers of toddlers and patterns of fulfilling the nutritional intake of stunted toddlers during the first 1,000 days. his life. This research uses a qualitative descriptive method using 7 activity methods which include observation, interviews, data collection on stunting families, preparation for stunting socialization, stunting socialization, documentation and evaluation.